2009
DOI: 10.5194/angeo-27-2607-2009
|View full text |Cite
|
Sign up to set email alerts
|

Gravity wave initiation of equatorial spread F/plasma bubble irregularities based on observational data from the SpreadFEx campaign

Abstract: Abstract. The data from ground based experiments conducted during the 2005 SpreadFEx campaign in Brazil are used, with the help of theoretical model calculations, to investigate the precursor conditions, and especially, the role of gravity waves, in the instability initiation leading to equatorial spread F development. Data from a digisonde and a 30 MHz coherent back-scatter radar operated at an equatorial site, Sao Luis (dip angle: 2.7 • ) and from a digisonde operated at another equatorial site (dip angle: −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
225
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 206 publications
(240 citation statements)
references
References 44 publications
15
225
0
Order By: Relevance
“…Previous studies have also suggested that initial density perturbations (seed waves) could play a significant role in the development of ESF (e.g. Abdu et al, 2009;Kherani et al, 2009;Tsunoda, 2010). The low ESF occurrence despite a significant PRE could be attributed to the absence of triggering perturbations.…”
Section: Monthly Variabilitymentioning
confidence: 98%
“…Previous studies have also suggested that initial density perturbations (seed waves) could play a significant role in the development of ESF (e.g. Abdu et al, 2009;Kherani et al, 2009;Tsunoda, 2010). The low ESF occurrence despite a significant PRE could be attributed to the absence of triggering perturbations.…”
Section: Monthly Variabilitymentioning
confidence: 98%
“…One is the difference in the zonal drift velocities of the EPBs due to different thermospheric zonal wind velocity from the Equator to middle latitudes and the other is the difference in the westward movement of the terminator (Huang et al, 2013). If one assumes that EPB seeding and development happen near the solar terminator passage and a successive EPB occurs soon after as the result of a periodic perturbation of the Flayer bottom side and the passage of the terminator (Tsunoda, 2006;Abdu et al, 2009;Takahashi et al, 2009;Makela et al, 2010). The distance between successive EPBs will, therefore, be determined by the velocity of the EPB and the terminator movement.…”
Section: Latitudinal Dependence Of Inter-bubble Distancesmentioning
confidence: 99%
“…Characteristics of EPBs have been extensively studied using different techniques such as VHF radars (Tsunoda, 1981;Abdu et al, 2009), rockets Muralikrishna et al, 2007), ionosondes (Abdu et al, 1983(Abdu et al, , 2003(Abdu et al, , 2012, optical imagers (Pimenta et al, 2003;Arruda et al, 2006;Paulino et al, 2011), GNSS receivers (De Rezende et al, 2007;Takahashi et al, 2014Takahashi et al, , 2015, and satellites (Huang et al, 2002(Huang et al, , 2013McNamara et al, 2013;Park et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Abdu et al (2009) andTakahashi et al (2010), the ascension rate of the bottom-type and/or bottomside F layer is representative of the zonal electric field of F irregular structures under the modulation of wave-like disturbance. This leads to numerous studies (e.g., Alam Mukherjee and Patra, 2014;Kherani and Patra, 2015) aiming to understand the physical origin of this valleytype plasma irregularity through the possible link with the fringe field (polarization field) of F irregularities.…”
Section: Langmuir Probe Measurementsmentioning
confidence: 99%